A simple method to assess the impact of sealing, headspace mixing and pressure vent on airtightness of manually closed chambers. Issue 1 (2nd March 2017) - Hoffmann, Mathias; Pehle, Natalia; Huth, Vytas; Jurisch, Nicole; Sommer, Michael; Augustin, Jürgen
Abstract: Within a full‐factorial laboratory experiment, three different designs and two modifications of typical manual closed chamber setups were tested for sealing integrity. Tests were performed using a simple method, based on injections of single CO2 pulses. Chamber designs differed in V:A‐ratio and chamber‐collar sealing (water, rubber‐foam, rubber‐tube). All chambers were tested with and without pressure vent and fan. Our results indicate significant differences in sealing integrity due to chamber‐collar sealing strategy. Especially rubber sealing turned out to be characterized by a certain non‐reliability. The effect of vent and fan, however, was of minor importance. The proposed setup is an effective way to assess the airtightness of manual chambers for subsequent field studies.